Food for Thought: The Politics of Financialization in the Agrifood System. (August 2013) - Fuchs, Doris; Meyer-Eppler, Richard; Hamenstädt, Ulrich
A number of scholars have started to investigate issues specifically associated with financialization in the agrifood sector. This article draws on this literature to map the dimensions of financialization and their interaction at different levels. In contrast to studies that have emphasized the economic preconditions and consequences of the financialization of agrifood, we are interested in the political forces and processes behind these developments. Our argument intends to demonstrate that the politics of financialization take a pervasive and multi-faceted form. Indeed, if one wants to identify and assess what drives and facilitates financialization and its diffusion, one needs to study political developments at all societal and political levels and in a variety of shapes and forms. In consequence, this analysis also serves to highlight the challenges involved for anyone aiming to foster a definancialization of the global agrifood system or of the global economic system as such.